Understanding hate crimes : acts, motives, offenders, victims, and justice - Turpin-Petrosino, Carolyn, 1952- (New York : Routledge, 2015)
'Hate crimes and lesser acts of bigotry and intolerance are constants in today's world. Since 1990 the federal government has monitored hate crime incidents in the United States. While the numbers are disturbing, even more devastating is the impact of these crimes on individuals, communities, and society. This comprehensive textbook serves as a stand-alone source for instructors and students who study hate crimes and/or other related acts. This text invites consideration of relevant social mores and practices as well as criminal justice policy as they relate to hate crimes by presenting a thorough and complete presentation of the subject in context. A comprehensive single source, efficient and a useful option for both instructors and students which also assesses hate crimes policy'--
Includes bibliographical references and index.
Keywords: Hate crimes -- United States; Violence -- Psychological aspects; Criminal psychology -- United States